Consumer Preference for Soft Drinks: An Analysis of Ingredients, Quality, and Flavor - Manandhar, Raju Bhai (PYC Nepal Journal of Management, 2023)
The rising demand for soft drinks in Nepal has prompted a keen focus on product features that cater to consumers’ expectations. The objective of the study is to examine the impact of ingredients, quality, and flavor on consumers’ preference for soft drinks. The study adopted descriptive and analytical research design. Primary data was collected through a five-point Likert scale questionnaire survey administered to respondents within the Kathmandu Valley using a convenience sampling technique. The study employed various statistical tools, including cross tab, standard deviation, independent sample t-test, correlation, and regression, to analyze the gathered data. The results revealed that quality exhibited the highest positive correlation with consumers’ preference for soft drinks, while flavor demonstrated the lowest correlation. Furthermore, it was found that both ingredients and quality significantly influenced consumer preference, whereas flavor did not have a significant impact. Gender also played a role in influencing consumer preference, affecting flavor but not ingredients and quality. The study emphasized the pivotal role of quality in ensuring customer satisfaction, while ingredients contributed to the creation of value for soft drinks. As such, companies need to uphold high-quality standards to meet consumer expectations effectively. The findings of this research provide valuable insights into consumer preferences for soft drinks and underscore the importance of product quality. Future researchers are encouraged to explore consumer preferences with larger sample sizes and robust methodologies, incorporating additional independent variables to gain a more comprehensive understanding of the soft drink market in Nepal.